Towards an open global Wi-Fi indoor positioning system via implicit crowdsourcing - Zhang, Dezhi (2017)
Location-based Services (LBSs) are important building blocks for a wide spectrum of context-aware applications. The Global Positioning System (GPS) has provided almost ubiquitous positioning services in outdoor environments and enabled many outdoor LBSs such as routing navigation, location check-in and field analysis. However, the indoor LBSs equivalents, e.g., routing the visually-impaired, are not yet pervasively available due to many unaddressed challenges in indoor positioning system deployments. The overarching goal of this project is to develop practical systems to address such challenges and finally build an Open Global Indoor Positioning System (OGIPS). OGIPS is a supplementation to GPS indoors and the combination of OGIPS and GPS is anticipated to provide truly global positioning services to virtually anyone.